2015
DOI: 10.1093/eurpub/ckv039
|View full text |Cite
|
Sign up to set email alerts
|

Transitions between health care settings in the final three months of life in four EU countries

Abstract: End-of-life transitions between health care settings are common across EU countries, in particular late hospitalizations for people residing at home. Frequency, type and reasons for terminal hospitalizations vary between countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 39 publications
7
64
0
1
Order By: Relevance
“…In the SENTI-MELC Study, only 38% of the decedents had no transition in the last three months of life [33]. Our results are also consistent with a recently published international study, in which data were gathered retrospectively by general practitioners networks [3]; more than one in two patients experienced at least one transition in the last three months and 1 in 10 patients in the last three days of life. Compared to Spain, Italy and Belgium, patients in the Netherlands were transferred less often at the end-of-life, which might be due to the importance of primary palliative care in this latter country [3].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the SENTI-MELC Study, only 38% of the decedents had no transition in the last three months of life [33]. Our results are also consistent with a recently published international study, in which data were gathered retrospectively by general practitioners networks [3]; more than one in two patients experienced at least one transition in the last three months and 1 in 10 patients in the last three days of life. Compared to Spain, Italy and Belgium, patients in the Netherlands were transferred less often at the end-of-life, which might be due to the importance of primary palliative care in this latter country [3].…”
Section: Discussionsupporting
confidence: 90%
“…Many efforts are undertaken in Switzerland to enable older and/or chronically ill patients to stay home longer. However, as shown in previous foreign studies, one of the consequences might be an increased need for hospitalisations at the end-of-life [3,4]. On the one hand, hospitalisations might turn out to be necessary when patients become more dependent, as dying at home usually requires formal as well as informal care; dying in a hospital was almost four times more likely for those who only received informal care, in contrast to those who received combined formal and informal care [5].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In Belgium and Spain, for instance, many palliative care services are based in hospitals,37 and another study has shown that GPs in these two countries cited palliative care as the reason for more than one in three terminal hospitalisations (hospital admissions during which the patient died) 38. Our data showed that the involvement of multidisciplinary palliative care teams was associated with fewer late hospitalisations in Belgium and the Netherlands, but this was not so in Italy and Spain.…”
Section: Discussionmentioning
confidence: 42%
“…Second, in order to prevent hospital admissions for palliative patients, health services often focus on the implementation of ACP in the primary care setting and nursing homes [4][5][6][7][8][9][10][11]. However, still many palliative patients reside and die in the hospital setting [12][13][14][15][16]. When admitted to the hospital, palliative patients often experience the disease and treatment burden strongly.…”
Section: Introductionmentioning
confidence: 99%